L’évolution conceptuelle internationale dans le champ du handicap : enjeux socio-politiques et contributions québécoises - Patrick Fougeyrollas (Perspectives Interdisciplinaires sur le Travail et la Santé)
Disability is not a personal attribute. It is the situational outcome of the interaction between an individual with body or functional differences and a specific physical and social environment. This simple assertion coming from the Quebec social movement for the exercise of human rights and equalisation of opportunities of people with disabilities which started about thirty years ago and developed in the Quebec Classification : Disability Creation Process (DCP), was central in discussions and controversies highlighted during the revision process of the International Classification of Impairments, Disabilities and Handicaps (ICIDH) of the World Health Organization.The author underlines important steps in this Quebec and international dynamics, punctuated as much by scientific discussions than by socio-political alliances, barriers or compromises. His contribution comes from his unique perspective of participant observer at the heart of international committees and underground strategies.